Assessing the implementation of the family care team in the district health system of health region 2, Thailand. Issue 1 (1st February 2018) - Kitreerawutiwong, Nithra; Mekrungrengwong, Sunsanee; Wongwonsin, Artitaya; Phetphum, Chakkraphan
Abstract : Background: The family care team (FCT) was established to improve the quality of care. This study aimed to explore the perceptions of FCT implementation and describe the challenges inherent in implementing the FCT. Methods: Forty in-depth interviews were conducted. The interviewees consisted of five primary care managers in the provincial medical health office, five directors of community hospitals, five administrators in district health offices, ten subdistrict health-promoting hospital directors, representatives from ten local organizations, and five heads of village health volunteers. Data were collected in accordance with semistructured interview guidelines and analyzed by thematic analysis. Results: Participants' expressed their opinions through five themes: (1) the role and scope of practice, (2) the communication in collaboration of the FCT, (3) the management of the FCT, (4) the impact of the FCT on the team members' feelings and primary care performance, and (5) the main challenges, including the insufficiency of a teamwork culture and a biomedical approach. Conclusion: The information suggests the importance of issues such as the clarification of the team members' roles and managers' roles, communication within and across FCTs, and the preparation for training of interprofessionals to enhance collaborative management to achieve the optimal care for people in the district health system. Significance statement: This study was conducted to gain in-depth understanding of the implementation of the family care team (FCT) in Thailand and its challenges. Since there had been no previous qualitative study that combined views from primary care managers, community hospital directors, administrators in district health offices, subdistrict health-promoting hospital directors, local organizations, and heads of village health volunteers, this study filled the gap by integrating all the views of the stakeholders in implementing the FCT. It was found that the FCT requires a range of interprofessional collaboration that involves the role and scope of practice, the communication, the management, and the impact of the FCT. The main limitation of the FCT was the insufficiency of a teamwork culture, and a biomedical approach was needed to overcome the challenges.